10+9-c=-9+3c

Simple and best practice solution for 10+9-c=-9+3c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+9-c=-9+3c equation:


Simplifying
10 + 9 + -1c = -9 + 3c

Combine like terms: 10 + 9 = 19
19 + -1c = -9 + 3c

Solving
19 + -1c = -9 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
19 + -1c + -3c = -9 + 3c + -3c

Combine like terms: -1c + -3c = -4c
19 + -4c = -9 + 3c + -3c

Combine like terms: 3c + -3c = 0
19 + -4c = -9 + 0
19 + -4c = -9

Add '-19' to each side of the equation.
19 + -19 + -4c = -9 + -19

Combine like terms: 19 + -19 = 0
0 + -4c = -9 + -19
-4c = -9 + -19

Combine like terms: -9 + -19 = -28
-4c = -28

Divide each side by '-4'.
c = 7

Simplifying
c = 7

See similar equations:

| 5-2*7/2 | | -7-7q=-7-9q | | n/8+4=6 | | 5b^2-34b+24=0 | | x/12=8 | | 5-2*-7/2 | | n/2+4=6 | | 6+d=-10-d | | 17-63= | | x^3-8x^2+4x-32=0 | | n/8+5=10 | | -5-2v=-7v | | 3x+3x+3x=198 | | 6(5-4r)=6(4-5r) | | (4/(x+4))-(3/(x-4))=(2x/((x^2)-16)) | | 10+5v=7v-10 | | 6s+5s=-77 | | -g=g+8 | | -5-3y=-18 | | 8h+8=-2+10h | | 7b-5=2b-.5 | | x^3+4x^2-32x=128 | | x/10-2=4 | | -6r=9-7r | | y/17=-5 | | x+5x+(35+x)=385 | | -7=x/4+(-5) | | 2u^2=7u+4 | | 150-1/2= | | 1/6(2x-4)=7 | | 3v^2+9v+4= | | 8x-2/3=4(x+2) |

Equations solver categories